Initial butyrate producers during infant gut microbiota development are endospore formers. (20th August 2020) - Appert, Olivia; Garcia, Alejandro Ramirez; Frei, Remo; Roduit, Caroline; Constancias, Florentin; Neuzil‐Bunesova, Vera; Ferstl, Ruth; Zhang, Jianbo; Akdis, Cezmi; Lauener, Roger; Lacroix, Christophe; Schwab, Clarissa
Summary: The acquisition of the infant gut microbiota is key to establishing a host‐microbiota symbiosis. Microbially produced metabolites tightly interact with the immune system, and the fermentation‐derived short‐chain fatty acid butyrate is considered an important mediator linked to chronic diseases later in life. The intestinal butyrate‐forming bacterial population is taxonomically and functionally diverse and includes endospore formers with high transmission potential. Succession, and contribution of butyrate‐producing taxa during infant gut microbiota development have been little investigated. We determined the abundance of major butyrate‐forming groups and fermentation metabolites in faeces, isolated, cultivated and characterized the heat‐resistant cell population, which included endospores, and compared butyrate formation efficiency of representative taxa in batch cultures. The endospore community contributed about 0.001% to total cells, and was mainly composed of the pioneer butyrate‐producing Clostridium sensu stricto. We observed an increase in abundance of Faecalibacterium prausnitzii, butyrate‐producing Lachnospiraceae and faecal butyrate levels with age that is likely explained by higher butyrate production capacity of contributing taxa compared with Clostridium sensu stricto. Our data suggest that a successional arrangement and an overall increase in abundance of butyrate forming populations occur during the first year of life, which is associated with an increase of intestinal butyrate formation capacity.